2018
DOI: 10.1097/htr.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Using Robotics to Quantify Impairments in Sensorimotor Ability, Visuospatial Attention, Working Memory, and Executive Function After Traumatic Brain Injury

Abstract: Robotic measures allowed us to quantify a range of impairments specific to each subject, and offer an objective tool with which to examine these abilities after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…We identified a correlation between baseline reaction time and baseline PPT L , with no correlation to the remaining variables. A pediatric study of healthy controls and concussion patients found that nondominant hand PPT scores correlated with reaction time, initial distance ratio, and path length ratio in the visually guided reaching task [63]. This study also reported a correlation between nondominant hand PPT scores and hits with their nondominant hand in the object hit task.…”
Section: Discussionmentioning
confidence: 55%
“…We identified a correlation between baseline reaction time and baseline PPT L , with no correlation to the remaining variables. A pediatric study of healthy controls and concussion patients found that nondominant hand PPT scores correlated with reaction time, initial distance ratio, and path length ratio in the visually guided reaching task [63]. This study also reported a correlation between nondominant hand PPT scores and hits with their nondominant hand in the object hit task.…”
Section: Discussionmentioning
confidence: 55%
“…Assistive robots are now recognized as a potential platform from which to launch cognitive assessments 60,61 and cognitive interventions 15 in older adults, with the latter ranging from prolonging functioning in people with dementia 32 to protecting cognition in healthy older adults. 12 Given the efficacy of cognitive training in older adults without dementia, 11 in contrast to impaired learning and retention of new information in people with dementia, 62 targeting independently-living, older adults without dementia may be a particularly efficient and effective approach.…”
Section: Carmentioning
confidence: 99%
“…Therefore, incorporating these measures did not add to the utility of the object-hit test in quantifying upper extremity motor deficits related to SRC. Notably, in both this study and related trials, 6,24 the highest percentage of impairment in upper extremity object-hit test performance occurred in the number of objects hit, either with both hands or the nondominant hand, rather than measures of more specific aspects of performance. Possibly, simple evaluation of the number of objects hit may capture the summative effects of more subtle or specific (or both) deficits and lead to identification of higher percentages of impairment.…”
Section: Upper Extremity Measuresmentioning
confidence: 50%